2020
DOI: 10.1101/2020.07.13.20153114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of B-cell repertoires and emergence of cross-reactive responses in COVID-19 patients with different disease severity

Abstract: COVID-19 patients show varying severity of the disease ranging from asymptomatic to requiring intensive care. Although a number of monoclonal antibodies against SARS-CoV-2 have been identified, we still lack an understanding of the overall landscape of B-cell receptor (BCR) repertoires in COVID-19 patients. Here, we used high-throughput sequencing of BCR repertoires collected over multiple time points during an infection to characterize statistical and dynamical signatures of the B-cell response to SARS-CoV-2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 87 publications
(202 reference statements)
0
6
0
Order By: Relevance
“…IGHV1-69 and IGHV3-23 were among the top 7 and 10 antibodies detected, respectively, and some of the BCR heavy chains detected in the lung lobe were also frequently detected (9,12). Bulk BCR heavy chain analysis in the PBMCs from 19 patients showed that IGHV4 families expression levels were higher compared with those from HDs, whereas IGHV1-69 and IGHV3-23 were expressed at higher levels in the HD groups (8). However, it was indicated that IGHV1-69 was highly reactive against RBD-and IGHV3-23 against N-terminal domain (NTD)-sorted mAbs for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…IGHV1-69 and IGHV3-23 were among the top 7 and 10 antibodies detected, respectively, and some of the BCR heavy chains detected in the lung lobe were also frequently detected (9,12). Bulk BCR heavy chain analysis in the PBMCs from 19 patients showed that IGHV4 families expression levels were higher compared with those from HDs, whereas IGHV1-69 and IGHV3-23 were expressed at higher levels in the HD groups (8). However, it was indicated that IGHV1-69 was highly reactive against RBD-and IGHV3-23 against N-terminal domain (NTD)-sorted mAbs for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 94%
“…Understanding the diversity of BCRs, their response to SARS-CoV-2 infection, and detection of specific BCRs may help in the development of therapeutic antibodies for patients with COVID-19. The life cycle of SARS-CoV-2 has been revealed (3), and multiple studies have investigated the development of neutralizing monoclonal antibodies targeting the SARS-CoV-2 spike (S) protein (4)(5)(6)(7)(8)(9)(10)(11)(12). Candidate antibodies are usually obtained by analyzing BCRs in the peripheral blood mononuclear cells (PBMCs) obtained from patients with COVID-19 compared with those from healthy donors (HDs).…”
Section: Introductionmentioning
confidence: 99%
“…The RAPID output indicates that SRR12190252 and SRR12190293 have longer CDR3s compared to the reference groups (Figure 3B) (42). In addition, the COVID-19 samples have shorter deletions and longer insertions (Figures 3C, E) (43). SHM in the germinal center is the key process for antibody affinity maturation.…”
Section: Rep-seq Dataset Analysis Platformmentioning
confidence: 97%
“…'Public' antibodies, those that are raised independently across multiple individuals against an immunodominant epitope, are of high interest to several fields of research, from vaccinology to drug discovery (67)(68)(69). Several studies have already identified public SARS-CoV-2 response antibodies based on convergence towards particular clonotype lineages (12)(13)(14)(15)(16)(17)(18), but none have yet considered the fact that antibodies from different lineages can exert similar functions. As demonstrated above, structural clustering enables us to group together clonally-distinct antibodies with a high chance of engaging the same epitope.…”
Section: Structural Clusters Frequently Span Multiple Clonal Lineagesmentioning
confidence: 99%
“…As a result, leniency is often introduced to the clonotyping protocol, by lowering the sequence identity threshold to 80% (11), ignoring J-gene annotations, and/or only considering the heavy chain (VH-only clonotyping) (4). Convergent lenient VH-only clonotypes have been identified between multiple SARS-CoV-2 infected or convalescent individuals (12)(13)(14)(15)(16)(17)(18) and across different studies, for example the overlap between the clonotypes found by Galson et al (4) and Nielsen et al (19). Several papers have compared BCR sequences from individuals to verified SARS-CoV-2 binders in CoV-Ab-Dab and identified clonal similarities (e.g.…”
Section: Introductionmentioning
confidence: 99%